PENGARUH GAYA KEPEMIMPINAN DAN LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA PEGAWAI KECAMATAN KANOR , KABUPATEN BOJONEGORO - Sentosa, Bayu (Universitas Muhammadiyah Gresik, 2019)
This research is motivated by the lack of optimal work discipline of Kanor District Office staff in Bojonegoro Regency. The purpose of this study was to describe (1) the influence of the sub-district leadership style in the Kanor District Office in Bojonegoro district, (2), and the work environment towards the work discipline of the Kanor District Office staff in Bojonegoro, (3) the influence of leadership style and work environment on work discipline employees in the employee work environment in Kanor district, Bojonegoro district. The method used in this study is quantitative with the type of Explanatory Research. The population in this study amounted to 20 employees. A sample of 20 employees was determined using Simple Random Sampling. Data was collected through questionnaires, interviews and documentation. The results of the study show (1) the work discipline of the Kanor District of Bojonegoro Regency is at a moderate level or the quality is quite good. (2) Leadership style has a positive effect on employee work discipline at Kanor District Office in Bojonegoro Regency (3) The working environment is very influential on the work discipline of Kanor District Office staff in Bojonegoro Regency